HUBUNGAN PRAKTIK PEMBERIAN MAKAN DENGAN KEJADIAN BERAT BADAN KURANG PADA ANAK USIA 6-24 BULAN DI WILAYAH KERJA PUSKESMAS SIDOARJO - Irma Dwi Suryani; Dini Ririn Andrias (Universitas Airlangga, 2015)
There are many problems arise related to feeding practices and breastfeeding pattern among children aged 6-24 months which is not suitable with the recommendation, such as not exclusively breastfeeding until infant aged 6 months, prelactal food, introduction of soft food, semi solid or solid foods for children whose age appropriate feeding, and food diversity. This study aims to analyze the association between feeding practices and underweight of children under two. This study was an observational analytic study with cross-sectional design. Using structured questionaire, interview was conducted to 51 mothers or caregivers who have children aged 6-24 months old and was selected by simple random sampling technique in Bluru Kidul and Magersari, Sidoarjo. Underweight was obtained from anthropometry data. Weight was measured by using baby scale and digital scale. Result of this research showed that there was no significant association between underweight of children under two with predominant breastfeeding, food diversity, and meal frequency as well as 6 months exclusive beastfeeding and duration of breastfeeding (p>0,05). This study concludes that there is no association between breastfeeding patterns and feeding practices with underweight of children aged 6-24 months. It is necessary to conduct further research on finding association between feeding practices and underweight of children aged 6-24 months by standardized anthropometric measuring tools to confirm results of this study in the same location.Keywords: breastfeeding, children aged 6-24 months, feeding, underweight